INVENTORY CONTROL PLANNING CRAFTS OF PEARL LEATHER SKIN IN THE CITY OF AMBON USING THE AGGREGATE METHOD - Pattiapon, Marcy L. (Tibuana, 2020)
Maluku is an archipelago that is rich innatural products, especially the sea includingpearl shells. One small industry that is quitedeveloped in the city of Ambon is the handicraftindustry made from pearl shells. pearl shells areutilized and treated as crafts with high artisticvalue is one of the characteristics of the Malukuregion which is one of the souvenir choices thatis quite attractive to domestic and foreigntourists. Besides being consumed, shellfish alsoproduce pearls and are often made into jewelrysuch as necklaces, bracelets, rings and wallhangings and various accessories.Fluctuationsin demand from time to time cause the need forinventory planning by forecasting the needs ofthe future. Forecasting used is the Time SeriesMoving Average and Single ExponentialSmoothing.Based on the results of researchconducted can be seen that the biggest capitalabsorbers are pearl shells, profiles, velvet clothand glass. Forecasting with Moving Average(MA) = 4 months has the smallest error valuewith forecast results is 57 kg. With a total costof Rp. 5,156,847,779. The alternatives used inaggregate planning are a strategy with regularregular working days and an overtime strategy,which is 26 days / month, with a productioncapacity of 39 units of finished shell products.With a total cost of Rp. 243,650,000.